UNDOING THE PAST THROUGH STATUTORY INTERPRETATION: THE CONSTITUTIONAL COURT AND MARRIAGE LAWS OF APARTHEID - Wessel le Roux (Obiter, 2022)
Recent legal scholarship has increasingly focussed on the way in which the law can be employed as a strategy of memory in post-conflict societies. War crimes trials, civil reparation or restitution claims, and the like, have all been extensively discussed as memorial practices. However, the way in which ordinary process of statutory interpretation can be employed to undo the past has thus far received little or now attention. In this article I investigate how the South African Constitutional Court has approached the interpretation of a number of apartheid marriage laws under sections 35(2) of the interim and 39(2) of the final Constitutions. I argue that, far from adopting a purposive approach to statutory interpretation as is often claimed, the court has in fact adopted a very narrow textual approach to statutory interpretation. I claim that this approach to the legislative legacy of the past is both hermeneutically and politically suspect. What is more, it discloses a predilection for monumental, as opposed to, memorial practices of memory.